2018
DOI: 10.1017/s1355617718000061
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term Psychosocial Functioning and Health-Related Quality of Life in Children and Adolescents With Prior Concussions

Abstract: Children's functioning before a concussion is critical to understanding outcome. Pre-injury attention and mood concerns should be assessed in clinical settings to prevent and treat long-term psychosocial problems after concussion. (JINS, 2018, 24, 540-548).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
1
13
1
Order By: Relevance
“…Our findings and those of other researchers suggest that individuals with concussion are prone to internalized psychological concerns, at least while they are symptomatic. A recent study by Plourde, Yeates, and Brooks (2018) did not find group differences on psychosocial measures at approximately 36 months after injury (vs. 2 months postinjury in this study), so it appears that academic and emotional concerns after concussion do subside over time.…”
Section: Discussioncontrasting
confidence: 53%
“…Our findings and those of other researchers suggest that individuals with concussion are prone to internalized psychological concerns, at least while they are symptomatic. A recent study by Plourde, Yeates, and Brooks (2018) did not find group differences on psychosocial measures at approximately 36 months after injury (vs. 2 months postinjury in this study), so it appears that academic and emotional concerns after concussion do subside over time.…”
Section: Discussioncontrasting
confidence: 53%
“…This is consistent with our previous longitudinal study of HRQOL among adolescent SRC patients 34 and a more recent study that demonstrated no persistent impairments in HRQOL or psychological functioning among adolescents with a history of one or multiple concussions compared to those with an orthopedic injury. 31 Our results have potentially important implications for the clinical management of acute pediatric SRC patients. Although most pediatric SRC patients will attain neurological recovery within 1-4 weeks, an important proportion will experience persistent symptoms that contribute to delayed clinical recovery.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have found that demographics (sex and age), medical history, history of psychiatric disorders, and neurodevelopmental conditions are associated with prolonged symptoms postconcussion. 6,7,11,14,17,[55][56][57][58] In addition, individuals with lower preinjury resiliency scores had increased concussion and anxiety symptoms 1 week and 1 month postinjury. 59 Our results demonstrate that preinjury symptoms captured with the PCSI (physical and emotional), personal characteristics such as age and sex and time from injury to ED, and parental postinjury physical symptom ratings explained most of the variance in PPCS at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of acute and subacute postconcussion symptoms5 and acute physical and fatigue symptoms such as headache, sensitivity to noise, balance, and fatigue have been associated with PPCS 6,7. Premorbid factors8 such as somatic symptoms,9 migraine,6 preinjury cognitive ability,10 preexisting attention and mood concerns,11 anxiety,12 coping strategies,13 family functioning, and parental psychological adjustment14,15 have also been associated with PPCS. Premorbid conditions may impede recovery processes16 and exacerbate concussion and premorbid symptoms such as in mood and psychiatric disorders 17.…”
mentioning
confidence: 99%